Interest of Muslim Youth: Purchasing Halal Korean Restaurants in West Java - Nuralam, Firly; Akbar, Nashr (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: The objective aim this study is to investigate the factors influencing young Muslims' inclinations in West Java to purchase Korean food through visits to Halal-certified Korean restaurants, Employing the Knowledge-Based Theory of Planned Behavior (TPB) framework as the main variables under investigation.Design/Method/Approach: The research methodology utilizes purposive sampling, targeting individuals aged between 16 and 30 years old. Data analysis employs the Structural Equation Modeling with Partial Least Squares (PLS-SEM) method.Findings: Consumer knowledge exerts a positive and notable influence on attitudes, similar to the effects observed with attitudes and subjective norms, which positively and significantly influence the interest of Muslim youth in Halal-certified Korean restaurants. However, perceived behavioral control variables could not be identified as factors significantly influencing the purchase interest of Muslim youth in MUI-certified Halal Korean restaurants.Originality/Values: This article presents several updates, including geographical scope limitations, explanations of the variables used, and novelties in the research period. It is anticipated that the research's findings will significantly enhance marketing tactics and the administration of Halal-certified Korean restaurants in the culinary industry. Additionally, it is hoped that it will also assist business players in this sector in understanding the factors driving the purchase interest of Muslim youth to increase visits to Halal-certified Korean restaurants.